Co3O4 nanobelt arrays assembled with ultrathin nanosheets as highly efficient and stable electrocatalysts for the chlorine evolution reaction. Issue 26 (20th June 2018) - Zhu, Xianglin; Wang, Peng; Wang, Zeyan; Liu, Yuanyuan; Zheng, Zhaoke; Zhang, Qianqian; Zhang, Xiaoyang; Dai, Ying; Whangbo, Myung-Hwan; Huang, Baibiao
Abstract : We report Co3 O4 nanobelt arrays (NBAs) assembled with ultrathin nanosheets prepared on fluorine doped tin oxide (FTO) substrates as electrocatalysts for the CER. Abstract : The chlorine evolution reaction (CER) is an important electrochemical process in chemical industry, but commonly used CER electrocatalysts are based on scarce elements e.g. Ru and Ir. Thus, it is necessary to develop efficient electrocatalysts based on more abundant elements. Here, we report that Co3 O4 nanobelt arrays (NBAs) assembled with ultrathin nanosheets which are less than 2.3 nm thick prepared on fluorine doped tin oxide (FTO) substrates are an example of such CER electrocatalysts. The Co3 O4 NBA anode is better than RuO2 -based anodes in terms of CER activity and is far more stable than RuO2 -based anodes.